Chemoenzymatic dynamic kinetic resolution of rac-1-phenylethanol in ionic liquids and ionic liquids/supercritical carbon dioxide systems. - Lozano, Pedro; De Diego, Teresa; Larnicol, Mickaël; Vaultier, Michel; Iborra, José L. (Biotechnology Letters, 2006)
Continuous dynamic kinetic resolution processes in different ionic liquid/supercritical carbon dioxide biphasic systems were carried out by simultaneously using both immobilized Candida antarctica lipase B (Novozym 435) and silica modified with benzenosulfonic acid (SCX) catalysts at 40 degrees C and 10 MPa. SCX was seen to act as an efficient heterogeneous chemical catalyst for the racemization of (S)-1-phenylethanol in different ionic liquid media ([emim][NTf(2)], [btma][NTf(2)] and [bmim][PF(6)]). Coating both chemical and enzymatic catalysts with ILs greatly improved the efficiency of the process, providing a good yield (76%) of (R)-1-phenylethyl propionate product with excellent enantioselectivity (ee = 91-98%) in continuous operation.